Infant Hearing Screening at Immunization centers-An early experience - Adhikari, Arun; Khatri, Bijay; Mathema, Luna; Poudyal, Prasanta; Chaudhary, Preeti; Upadhyay, Sanjib kumar; Shrestha, Rajan; Upadhyay, Madan Prasad; Kafle, Kumud Kumar (Health Prospect, 2024)
In low-income countries, deaf children are identified late due to the absence of newborn hearing screening. Along with speech-related disability, hearing impairment is a common yet neglected disability in developing countries like Nepal. Great emphasis is placed on the importance of early detection, reliable diagnosis, and timely intervention with better chances of hearing-impaired infants developing skills equivalent to their peers. In Nepal, the institutional delivery is comparatively lower than the routine vaccination coverage. Newborn screening at the delivery center may miss more than 40% of newborns as only 57% are delivered in health institutions, whereas vaccination coverage under National Immunization Program among infants is about 90%. Infant hearing screening (IHS) at immunization centers can be an alternative to universal newborn hearing screening in countries with lower institutional delivery rates. We are sharing our early experiences on implementing the program where there is no government guidance on IHS.